PERSEPSI PENGURUS LINGKUNGAN STASI SANTA MARIA RATU DAMAI SLAHUNG PONOROGO TENTANG HAKEKAT LINGKUNGAN - Wilhelmus, Ola Rongan; Suparlis, Yulius (Bahasa Indonesia, 2023)
Basic Christian Community is a way of life for the Church of Christ's disciples in society. The community is present in the midst of society to live out and proclaim the Gospel of Christ for families and society through fellowship, worship, preaching, witnessing and community service. Many members and administrators of the community do not understand and appreciate well and deeply the nature of the Basic Christian Community. The research was conducted with the aim of analyzing the understanding of Basic Christian Community administrators regarding the nature of the community. The research was carried out using a quantitative approach, and the type of research was a survey. The research respondents consisted of the community administrators at the Santa Maria Ratu Damai Slahung Station, Ponorogo. The main variables of this research are the Basic Christian Community, the purpose and function of the community, community members and administrators, and the relationship between the parish and the community. The results of the research data analysis revealed that majority of respondents perceived that Basic Christian Community is the way of life for Christ's disciples in the Church. The results of the research data analysis also indicated that the community was formed with the aim of experiencing the 5 aspects of Church life (fellowship, worship, preaching, witnessing and community service) both in the family and society.